2021
DOI: 10.3390/jcm10091885
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Uric Acid Level Is Related to the More Severe Renal Histopathology of Female IgA Nephropathy Patients

Abstract: Hyperuricemia is a significant risk factor for cardiovascular morbidity and chronic kidney disease progression. IgA nephropathy (IgAN) is a well-known primary glomerular nephropathy. Hyperuricemia is associated with a poor prognosis in IgAN patients. We evaluated the association of hyperuricemia with the histopathological severity of IgAN in male and female patients; 658 patients diagnosed with IgAN via kidney biopsy were initially included. Baseline patient data were collected by eight university hospitals af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Therefore, our study indicated that the TA-SUA offers a better predictor of renal prognosis than the baseline SUA level. However, SUA is reported to be related to more severe renal histopathology and worse prognosis in female IgAN patients ( Choi et al, 2021 ; Oh et al, 2020 ). At present, it is not clear why the serum uric acid level of women is more important than that of men, but it has been reported that estrogen can inhibit urate transporter 1, reduce serum uric acid level and promote urinary acid excretion ( Takiue et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study indicated that the TA-SUA offers a better predictor of renal prognosis than the baseline SUA level. However, SUA is reported to be related to more severe renal histopathology and worse prognosis in female IgAN patients ( Choi et al, 2021 ; Oh et al, 2020 ). At present, it is not clear why the serum uric acid level of women is more important than that of men, but it has been reported that estrogen can inhibit urate transporter 1, reduce serum uric acid level and promote urinary acid excretion ( Takiue et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid, the product of purine metabolism, is a white tasteless odorless crystalline, which is primarily cleared by the kidneys. Notably, abundant evidence has confirmed hyperuricemia, featured with an increase in serum uric acid, mediates renal impairment via a variety of mechanisms, which include oxidative stress, nitric oxide pathway alteration, insulin resistance (IR), fructose metabolism disorder, inflammatory activation, stimulation of the renin-angiotensin system, and endothelial dysfunction 6 , 22 , 23 . The UAR, a valuable and compositive index that reflects the status of metabolic disturbance, nutrition and inflammation, possess the advantages of could be acquired timely and easily from initial serum biochemical analyses with low extra health cost, might be a novel predictor for renal progression and contribute to targeted management in the IgAN population.…”
Section: Discussionmentioning
confidence: 99%
“…As the final product of purine metabolism, uric acid (UA) is associated with oxidative stress, inflammatory response and endothelial dysfunction [5]. To date, hyperuricemia, which is presented as elevated serum uric acid level and associated with metabolic derangement, has attracted widespread attention as a reliable prognostic indicator for IgAN progression [6,7], and may contributes to renal injury Ivyspring International Publisher through the activation of Wnt5a/Ror2 or the NADPH/ROS/ERk1/2 signaling pathway [8]. Albumin (ALB), synthesized by the liver, is a negative acute phase reactant whose level in the blood decreases during malnutrition and inflammation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…
Hyperuricemia (HUA) is closely related with gout [1, 2], nephropathy [3,4], and cardiovascular risk [5]. Lacking the functional uricase, hominoids are the only mammals that cannot degrade urate [6].
…”
mentioning
confidence: 99%